2004
DOI: 10.1029/2004jd004747
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of individual airborne particles by using aerosol time‐of‐flight mass spectrometry at Mace Head, Ireland

Abstract: [1] An aerosol time-of-flight mass spectrometer was deployed at Mace Head (Ireland) during August 2002. The measurements provide qualitative chemical composition and size distribution (0.3-3 mm) information for single particles. Three broad categories of particles: sea salt, dust, and carbon-containing particles were identified and apportioned, and their temporal evolution (1 hour resolution) is described. Aerosol sources were correlated with meteorological factors and with air mass trajectories, demonstrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 53 publications
(84 reference statements)
8
83
0
Order By: Relevance
“…Both sea salt classes are typical of those observed in other coastal/marine environments (Gard et al, 1998;Dall'Osto et al, 2004;Healy et al, 2010). Average mass spectra are shown in Fig.…”
Section: Sea Saltmentioning
confidence: 86%
“…Both sea salt classes are typical of those observed in other coastal/marine environments (Gard et al, 1998;Dall'Osto et al, 2004;Healy et al, 2010). Average mass spectra are shown in Fig.…”
Section: Sea Saltmentioning
confidence: 86%
“…It is important to note that KeNa-rich type was observed in 11.9% of the particles. The color stacks of the carbon cluster ions peak demonstrate that approximately 90% of the KeNa-rich particles internally mixed with EC ( Figure S3), which differs from the sea salt particles (Dall'Osto et al, 2004;Dall'Osto and Harrison, 2006;Spencer et al, 2008). Pearson correlation analysis indicated that the unscaled SPAMS counts in 1 h resolution of certain particle types have a correlative relationship, particularly between KeEC and KeNarich (correlation coefficients r ¼ 0.894, p < 0.01) ( Table S1).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The ATOFMS (TSI model 3800) was fitted with an aerodynamic lens (TSI model AFL100) for the measurement of particles in the size range 100-3000 nm. The instrument is described in detail elsewhere (Dall'Osto et al, 2004). In short, particles are sampled through an orifice and accelerated through the aerodynamic lens to the sizing region of the instrument.…”
Section: Sampling Site and Equipmentmentioning
confidence: 99%